“To venner”: – tvesynet i arbejde hos Pontoppidan - Gunder Hansen, Nils (Pontoppidaniana, 2025)
Abstract Henrik Pontoppidan has often been praised for his “double vision,” yet the concept has remained somewhat vague and is today regarded as theoretically outdated, especially when compared to Mikhail Bakhtin’s notion of polyphony. In this essay, Nils Gunder Hansen proposes that the concept of double vision should be detached from ideas of authorial psychology and narrative perspective and instead be understood as something that takes place within the text itself. As an example of this double vision at work, he examines Pontoppidan’s depiction of the interpersonal psychology of friendship in the short story “To Venner” from the collection Skyer (1890). He further suggests that the story may help us gain insight into the nature of friendship – and into the political and ideological disagreements between friends – in our own lives.